Antibody mediated drug delivery systems - edited by Yashwant Pathak; Simon Benita (Wiley, 2012)
This book covers various aspects of antibody mediated drug delivery systems - theoretical aspects, processing, viral and non-viral vectors, and fields where these systems find and /or are being evaluated for applications as therapeutics and diagnostic treatment. Chapters discuss actual applications of techniques used for formulation and characterization. Applications areas include cancer, pulmonary, ocular diseases; brain drug delivery; and vaccine delivery. The contributing authors represent over 10 different countries, covering recent developments happening around the globe